Ensino colaborativo e educação física: contribuições à inclusão escolar - Oliveira, Valéria Manna (2014)
In Brazil, special education public is a challenge to all teachers, especially to Physical Education ones. Among others, it encompasses students with disabilities, students with intellectual giftedness, and students with pervasive developmental disorder. Besides posing challenges, the inclusion process causes worry and generates debates on problems that impede the full partaking of such pupils in schooling practices related to physical education. This thesis presents a research that focused on these matters by means of co-working involving the researcher and the Physical Education teacher in regular classrooms following co-teaching perspective. The starting point of the research is the following question: what contributions co-working involving Physical Education teacher and researcher may provide to people with disabilities and to Physical Education teacher in regular schools attended by students who are the special education’s target? The research aimed at discussing and analyzing the development of such co-working activity involving the researcher and Physical Education teacher. It followed co-teaching perspective and was put into practice in a public school in Uberlândia, state of Minas Gerais. Participant qualitative approach, which recognizes relations between social sciences and intervention in social reality, was the methodological choice to develop the research in three phases: 1) making the research; 2) intervening in social reality; 3) assessing/diagnosing it. Strategies to gather data included semi structured interview, questionnaire, participant observation, and group interview. Data come, above all, from oral accounts as well as from the work by the group of participants of the research, which means, researcher, Physical Education teacher who works at regular schools and three teachers who deal with AEE (Atendimento Educacional Especial), a special educational teaching program. The concept of inclusion is discussed accordingly to authors such as Miranda (2001), Mantoan (2001), Duarte and Santos (2003), Mittler (2003), Rodrigues (2006), and Bueno (2008). The conception of co-working is developed in the light of studies by Capellini (2004) and Mendes (2009), among others. Results point out not only initial conditions of anguish, doubts and hardships, but also a will to debate difficulties Physical Education teachers face in their daily pedagogical activities at school. Likewise, results showed that teachers who took part in the research are interested in continuing their training in connection with co-teaching as strategy to teach physical education at inclusive schools.